Environmental disobedience and the dialogic dimensions of dissent. Issue 2 (23rd February 2017) - von Essen, Erica
ABSTRACT: In this paper, the potential for applying deliberative disobedience as a legitimation framework for environmental disobedience is unpacked. At present, disobedience on behalf of non-humans is not justified within the liberal theory of disobedience put forward by Rawls. Instead of framing harms to environment as indirect harms to humans, Smith's framework of deliberative disobedience may be invoked on the premises that disobedients publicize not fundamental rights violations, but systematically distorted communication in the process that enacted the environmental policy or decision. To this end, the paper engages in a critical discussion about the dangers of legitimating environmental disobedience through deliberative disobedience. Indeed, its justification hinges on possessing deliberative or "dialogic" credentials as an alternative mode of address to distorted official channels. But its consequence, that of characterizing environmental disobedience as dialogic, means embracing the increasingly violent, clandestine and coercive acts as dialogue. I argue, this from deliberative premises with precarious implications for the legitimacy and uptake of environmental disobedients.